Re-thinking shaming Practices in African [Igbo] Traditional Society as a Viable Option for Maintaining Justice, Social Integration and Moral Development in Modern Africa - Okoro, Kingsley (Advances in Social Sciences Research Journal, 2016)
The history of crime dates back to historical antiquity and this is an outgrowth of human capriciousness and avarice, which made everyone an atom and a law unto himself in the social order. This situation hinders human mutuality and cooperation which is needed for human survival, development and progress. Guided by reason, man had to notch out morns/ laws that will guide human relationship and maintain social justice. These rules have been notched with their consequences. The technical name for the consequences is “Shaming” Shaming practices vary according to the degree of offence and in relations to time and context. While some shaming practices involve capital punishment others involve reprimanding, which may include the incarceration of the offender in prison and subsequent parole. However, the overall aim of shaming is social cleansing of the society that has been desecrated by the criminal act. Nevertheless, this paper notes that the present shaming model is alien to African [Igbo] culture and as such have failed to achieve its purpose. Therefore, it begins a re-thinking of an indigenous shaming model that allies with African culture as to bring about the positive social effect of shaming ideality in the society and this is the resocialization and reintegration of the offender into the society after a period of shaming ritual. Using the socio-anthropological method, this paper underscores the if African [Igbo] indigenous shaming model is adopted as a means of adjudicating social justice in the modern era our dream of crime free African society shall soon be realized.